Nanoparticles for Enhanced Adoptive T Cell Therapies and Future Perspectives for CNS Tumors - Balakrishnan, Preethi Bala; Sweeney, Elizabeth E. (Frontiers in Immunology, 2021)
Adoptive T cell therapy has emerged as a revolutionary immunotherapy for treating cancer. Despite immense promise and clinical success in some hematologic malignancies, limitations remain that thwart its efficacy in solid tumors. Particularly in tumors of the central nervous system (CNS), T cell therapy is often restricted by the difficulty in intratumoral delivery across anatomical niches, suboptimal T cell specificity or activation, and intratumoral T cell dysfunction due to immunosuppressive tumor microenvironments (TMEs). Nanoparticles may offer several advantages to overcome these limitations of T cell therapy, as they can be designed to robustly and specifically activate T cells ex vivo prior to adoptive transfer, to encapsulate T cell stimulating agents for co-localized stimulation, and to be conjugated onto T cells for added functionality. This perspective highlights recent preclinical advances in using nanoparticles to enhance T cell therapy, and discusses the potential applicability and constraints of nanoparticle-enhanced T cells as a new platform for treating CNS tumors.